AKTIVITAS ANTIOKSIDAN, SIFAT FISIK DAN SENSORIS MARSHMALLOW MELON (Cucumis melo L.) DENGAN PENAMBAHAN EKSTRAK BIT MERAH (Beta vulgaris L. var. Conditiva) - Gumansalangi, Frysye; Djarkasi, Gregoria S. S. (Fakultas Pertanian, Universitas Sam Ratulangi, 2019)
The purpose of this study was to determine the impact of red beet extract addition to melon marshmallow product towards the antioxidant activities, physical characteristic and sensory properties. The method that used in this study were folin ciocalteu methods for total phenol test, DPPH (1,1-diphenil, -2 picrylhydrazyl) method that used for the antioxidant activity test, penetrometer methods was used for hardness test, and hedonic scale for the sensory test. The result of this study showed that 15% addition of red beet extract was the best treatment towards antioxidant activities which has 83,42% inhibitions, IC50 value of 145,27 Âµg/mL. Furthermore, the treatment of 15% red beet extract addition also showed physical characteristic value (hardness) of 79,78 mm/g/s which is the closest value to commercial marshmallow. The treatment which has the best result of sensory properties was 10% red beet extract addition, that is 3,34 (neutral). Keywords: Antioxidant, Red Beet, Melon, Marshmallow